PMM.35 Comprehensive Tools in Assessing Risk of Pre-term Labour: History and Cervical Length. (9th June 2014) - Rice, A; Palaniappan, N; Mary, N
Abstract : Background: Screening methods to determine risk for pre-term delivery include robust history taking and cervical length assessment. A cervical length of <15mm has shown to have a 50% risk of preterm delivery prior to <32 weeks. 1 Methods: Retrospective analysis of all cervical length scans done over a 3 year period for women classed as high risk of pre-term delivery (7000 deliveries/ year). Results: 256 patients underwent cervical length scanning for a previous history of LLETZ treatment, preterm labour, mid-trimester fetal loss or uterine abnormalities. Of these patients 223 (87%) patients had cervical length of >25 mm and were therefore categorised as low risk. 14% delivered prior to 37 weeks and 86% delivered at term. This gives a sensitivity of 75% (95% CI: 59.66 % to 86.79%) and negative predictive value of 95% (95% CI: 91.27% to 97.49%) when initial cervical length is >25 mm. 28(11%) patients were found to have a cervical length between 15 mm and 25 mm and 5(2%) had a cervical length <15 mm. Of the patients with cervical length between 15 mm and 25 mm, 14% delivered at <28 weeks, 11% at <34 weeks, 18% at <37 weeks and 57% delivered at term. Of the 5 patients who had cervical length of <15 mm (40%) delivered at <28 weeks and 1 (20%) had a delivery <34 weeks with the remaining 40% delivering at term. Conclusions: Our methods of screening using history and cervical length assessment appear to be robust in predicting pre-term deliveries with >40% of our predicted patients delivering pre-term. Reference: Chandiramani M, Shennan AH. Cervical insufficiency: prediction, diagnosis and prevention. The Obstetrician and Gynaecologist 2008;10:99–106